Extraction, purification and characterization of the crystallin protein of cataractous eye lens nucleus. Issue 18 (21st September 2015) - Sher, Muhammad; Hameed, Ayesha; Noreen, Sobia; Fayyaz-ur-Rehman, Muhammad; Hussain, Muhammad Ajaz; Bukhari, Syed Nasir Abbas
<x xml:space="preserve">Abstract</x> The purpose of this study is to separate and identify the crystallin protein present in the nucleus of a human cataractous eye lens.